2000
DOI: 10.1093/ajcn/71.5.1317s
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal metabolism of vitamin D

Abstract: During pregnancy, maternal serum concentrations of 25-hydroxyvitamin D, the circulating form of vitamin D, correlate with dietary vitamin D intake. Maternal serum concentrations of 1,25-dihydroxyvitamin D, the hormonal circulating and active form of vitamin D, are elevated during pregnancy; 1,25-dihydroxyvitamin D is synthesized mainly by the decidual cells of the placenta and allows for increased calcium absorption. The fetus is entirely dependent on the mother for its supply of 25-hydroxyvitamin D, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
170
0
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(196 citation statements)
references
References 61 publications
11
170
0
15
Order By: Relevance
“…Previous knowledge about this relationship was based on observational data (24,25) . For example, 25(OH)D in unsupplemented infants born to vitamin D-replete mothers in Finland decreased from~50 nmol/l at birth to <25 nmol/l by 8 weeks of age (25) , a finding that has been interpreted as evidence that the prenatal contribution to infant vitamin D status is limited to the first 2 months of life (16) , consistent with the present trial. Previous trials of maternal supplementation with 10 µg (400 IU) vitamin D daily starting in week 12 of pregnancy until delivery (17) or a bolus dose of 2500 µg (100 000 IU) vitamin D in month 6 or 7 of pregnancy (18) showed significant increases in infant 25(OH)D; however, infant follow-up in those studies was limited to the first week of life.…”
Section: Discussionsupporting
confidence: 89%
“…Previous knowledge about this relationship was based on observational data (24,25) . For example, 25(OH)D in unsupplemented infants born to vitamin D-replete mothers in Finland decreased from~50 nmol/l at birth to <25 nmol/l by 8 weeks of age (25) , a finding that has been interpreted as evidence that the prenatal contribution to infant vitamin D status is limited to the first 2 months of life (16) , consistent with the present trial. Previous trials of maternal supplementation with 10 µg (400 IU) vitamin D daily starting in week 12 of pregnancy until delivery (17) or a bolus dose of 2500 µg (100 000 IU) vitamin D in month 6 or 7 of pregnancy (18) showed significant increases in infant 25(OH)D; however, infant follow-up in those studies was limited to the first week of life.…”
Section: Discussionsupporting
confidence: 89%
“…In the absence of environmental and behavioural factors, 25OHD has been found to remain unchanged during pregnancy [7], while other evidence has indicated that 25OHD levels decline slightly with advancing gestation [8]. During pregnancy, 25OHD diffuses across the placental barrier, meaning the foetus relies entirely on the vitamin D status of the mother [9].…”
Section: Introductionmentioning
confidence: 99%
“…Increased synthesis of the active vitamin D form is due to the enhanced production of 1a-hydroxylase in the decidua and placenta, as well as an oestrogen-dependent increase in vitamin D binding protein [7]. This apparent rise in 1,25(OH) 2 D has led to the suggestion that pregnant women may require higher cellular exposure to active vitamin D during the second and third trimesters, and has been interpreted by some as providing evidence for its potential role in obstetric well-being [8].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-body mineral content triples between weeks 32-33 and 40-41 of gestation in humans (Salle et al, 2000). Despite this dramatic mineralization, the bones of infants contain more water and less fat, protein, and minerals than adult bones.…”
Section: 36mentioning
confidence: 99%